THE IMPLEMENTATION OF THE NUMBERED HEADS TOGETHER COOPERATIVE LEARNING MODEL TO IMPROVE STUDENTS’ BASKETBALL LEARNING OUTCOMES - Kadek Oka Satrya Wibawa; I Gusti Lanang Agung Parwata; I Ketut Sudiana (RADJA PUBLIKA, 2026)
This study aimed to improve students’ basketball learning outcomes through the implementation of the Numbered Head Together (NHT) cooperative learning model in class X.3 of SMA Negeri 2 Denpasar. This research employed Classroom Action Research conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The research subjects were 42 students. Data were collected through observation and basketball learning achievement tests and analyzed using descriptive quantitative techniques. The results showed an improvement in students’ learning outcomes after the implementation of the NHT cooperative learning model. The initial average score was 68.5 with a learning mastery percentage of 26.19%. In Cycle I, the average score increased to 74.1 with 61.9% learning mastery, and in Cycle II it further increased to 78.6 with 85.7% learning mastery. These findings indicate that the NHT cooperative learning model is effective in improving basketball learning outcomes and promoting active student participation in the learning process.